2020
DOI: 10.1080/21691401.2020.1770265
|View full text |Cite
|
Sign up to set email alerts
|

Localised delivery of quercetin by thermo-sensitive PLGA-PEG-PLGA hydrogels for the treatment of brachial plexus avulsion

Abstract: Accumulating evidence indicates that oxidative stress and inflammation are implicated in brachial plexus avulsion (BPA). Quercetin has anti-inflammatory, anti-oxidant, anti-apoptotic, and neuroprotective properties. This study investigated the therapeutic efficacy of a temperature-sensitive poly(D,L-lactide-co-glycolide)-poly(ethylene-glycol)-poly(D,L-lactide-co-glycolide) (PLGA-PEG-PLGA) hydrogel sustained-release system of quercetin in BPA. In situ injections of the hydrogel loaded with different concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…The results obtained suggested that oxidative damage and inflammation in the spinal cord were improved along with increase neuron survival rate and promotion in nerve regeneration and motor function recovery. The authors suggest that the sustainable approach of quercetin delivery has promising applications in the clinical treatment of brachial plexus avulsion (BPA) [112]. Based on the study carried out by Yu et al [113] the increase in the survival rate of PC12 injured by Aβ25-35, promotion of cell proliferation, and antagonization of the toxicity of Aβ due to quercetin, led it to be considered as a strong agent as a drug candidate for the treatment of Alzheimer disease.…”
Section: Quercetin As a Neuroprotective Agentmentioning
confidence: 99%
“…The results obtained suggested that oxidative damage and inflammation in the spinal cord were improved along with increase neuron survival rate and promotion in nerve regeneration and motor function recovery. The authors suggest that the sustainable approach of quercetin delivery has promising applications in the clinical treatment of brachial plexus avulsion (BPA) [112]. Based on the study carried out by Yu et al [113] the increase in the survival rate of PC12 injured by Aβ25-35, promotion of cell proliferation, and antagonization of the toxicity of Aβ due to quercetin, led it to be considered as a strong agent as a drug candidate for the treatment of Alzheimer disease.…”
Section: Quercetin As a Neuroprotective Agentmentioning
confidence: 99%
“…Similar rat or mouse models of upper-middle trunk and global trunk avulsion were successively reported to expound the mechanism of motor neuron degeneration and/or to evaluate different repair and reconstruction methods [ 39 41 ]. A most recent research of Huang et al [ 42 ] reported that the temperature-sensitive quercetin-loaded PLGA-PEG-PLGA hydrogel sustained-release system could promote nerve regeneration and motor function recovery during the early stage of BPA due to its intrinsic function of anti-inflammation, which had a good prospect from bench to bedside translation. Meanwhile, the posterior approach models also could be used in the field of neuropathic pain research according to recent work.…”
Section: Three Approaches Of the Animal Avulsion Modeling Procedurmentioning
confidence: 99%
“…Hydrogel scaffolds also have electrical conductivity and can simulate the electrophysiologic environment of nerve tissue in combination with exogenous ES. Hydrogels have been used for nerve repair through the delivery of small molecule drugs in a rat brachial plexus injury model [13].…”
Section: Introductionmentioning
confidence: 99%